KONSISTENSI PENERAPAN SANKSI PIDANA TERHADAP PELAKU PENISTA AGAMA DI INDONESIA - Basuki Basuki (LPPM Institut Pendidikan Nusantara Global, 2023)
The Indonesian constitution, namely the 1945 Constitution, is one of the instruments of human rights fulfillment, namely regulating the protection of religious freedom in Indonesia as stated in Article 27 paragraph (1), Article 28D paragraph (1), Article 28e, article 28i paragraph (1) and (2), Article 29 paragraph (2). In order to maintain the relationship between religious freedom and public order, the state makes restrictions on actions that are considered blasphemous or insulting to other religions that can trigger conflicts in public life. In this study raised two problems, namely how the consistency of the application of criminal sanctions against perpetrators of blasphemy in Indonesia ? and What is the form of updating the Criminal Code in realizing the consistency of the application of sanctions against perpetrators of religious blasphemy in Indonesia? The Theory of deferential Association by Edwin H. Sutherland and Emile Durkheim's theory of Anatomy. The method used is a normative juridical research method that begins the collection of legal materials carried out by identifying and inventorying positive legal rules, researching library materials (books, scientific journals, research reports), and other sources of legal materials relevant to the legal issues under study. The result of this study is that the consistency of the application of criminal sanctions against perpetrators of blasphemy in Indonesia. Has not been consistent and the Criminal Code (KUHP) relating to blasphemy needs to be renewed.